High-stress-resistance PMMA (Polymethyl Methacrylate) composite film, preparation method and flexible OLED (Organic Light Emitting Diode) device

By forming a nano-wrinkled flow-guiding structure on the surface of a PMMA film, the stress concentration problem in flexible OLED devices was solved, and a high-stress-resistant PMMA composite film was prepared, which improved the optical performance and flexibility of the device and extended its lifespan.

CN121471558APending Publication Date: 2026-02-06ANHUI HEMEI MATERIALS TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511565655.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-30
Publication Date
2026-02-06

AI Technical Summary

Technical Problem

Existing PMMA films in flexible OLED devices suffer from microcrack initiation and propagation due to stress concentration, affecting device lifespan and reliability. Existing modification solutions struggle to balance optical performance, flexibility, and processing compatibility.

Method used

A nano-wrinkled flow-guiding structure is formed on the surface of a PMMA film. Through a specific solution mixing and closed solvent vapor drying process, the functional nanofiller is uniformly dispersed and a nano-wrinkled flow-guiding structure is induced on the film surface to provide a stress-directed release path.

Benefits of technology

The fabrication of high-stress-resistant PMMA composite films has been achieved, which have high optical transmittance and flexibility, and are suitable for the use of devices such as polarizers, encapsulation films and light control films in flexible OLEDs, thus extending device life and improving reliability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to a high-stress-resistance PMMA composite film, a preparation method and a flexible OLED device.The preparation method comprises the steps that polymethyl methacrylate, a solvent and functional nano filler are fully mixed to form a film, the formed film is placed in a closed solvent steam environment to be slowly dried, a steam source is the solvent for dissolving the polymethyl methacrylate, the functional nano filler is taken as a functional nano filler, and the functional nano filler is taken as a functional nano filler to prepare the high-stress-resistance PMMA composite film. And inducing to form a nano wrinkled flow guide structure on the surface of the formed film to obtain the high-stress-resistance PMMA composite film. The composite film has excellent high optical transmittance, bending stress, curling stress and flexibility, and is adaptive to the use requirements of devices such as a polaroid, a packaging film and a light control film in a flexible OLED (Organic Light Emitting Diode).
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application relates to the technical field of optical films, in particular to a high-stress-resistance PMMA composite film, a preparation method and a flexible OLED device. BACKGROUND

[0002] PMMA is a commonly used polymer material for key components such as polarizing plates, encapsulating films and cover plates in OLED devices due to its high light transmittance, good processability and smooth surface. However, with the development of flexible OLEDs, the performance requirements of device thin films in repeated bending, curling assembly and other scenarios are increasingly stringent, and PMMA thin films are prone to stress concentration in such applications, which may cause micro-crack initiation and propagation, thereby seriously affecting the service life and reliability of OLED devices.

[0003] To alleviate this problem, researchers have tried various modification schemes, but it is difficult to simultaneously consider optical performance, flexibility and process compatibility: cross-linking enhancement can improve mechanical properties, but it may cause PMMA to become brittle and reduce bending life; nano-filler enhancement (such as the introduction of ZnO nanoparticles) may increase light scattering and cause a decrease in transparency; and non-textured design structures cannot guide natural stress release, resulting in uncontrollable crack concentration areas. Moreover, related technologies generally lack effective linkage between microstructure physical regulation and application requirements of flexible electronic devices, ultimately leading to the difficulty of PMMA thin films in meeting the comprehensive performance requirements of key components for flexible OLEDs. SUMMARY

[0004] To solve the above technical problems, the application provides a high-stress-resistance PMMA composite film, a preparation method and a flexible OLED device.

[0005] To achieve the above purpose, the application provides a preparation method of a high-stress-resistance PMMA composite film, comprising the following steps: S1, dissolving polymethyl methacrylate into a solvent to obtain a first mixed solution, wherein the polymethyl methacrylate accounts for 5% to 12% in terms of mass percentage; S2, adding functional nano-filler to the first mixed solution, and mixing uniformly after magnetic stirring and ultrasonic dispersion in sequence to obtain a second mixed solution, wherein the functional nano-filler accounts for 0.01% to 10% in terms of mass percentage; S3, coating the second mixed solution in step S2 on a flexible substrate to form a film; S4, slowly drying the film in step S3 in a closed solvent vapor environment, and inducing the formation of a nano-corrugated flow guide structure on the surface of the film to obtain a high-stress-resistance PMMA composite film, wherein the vapor source for forming the vapor environment includes the solvent in step S1.

[0006] As a further improvement of the present application, in step S1, the solvent is selected from any one of trichloromethane, ethyl acetate, and a mixture of acetone / isopropyl alcohol.

[0007] As a further improvement of the present application, in step S2, the functional nanofiller is selected from any one of silicon dioxide nanoparticles, graphene oxide, and TEMPO-oxidized nanocellulose.

[0008] As a further improvement of the present application, in step S2, before the magnetic stirring and ultrasonic dispersion, the process of adding a non-ionic surfactant to the first mixed solution is further included.

[0009] As a further improvement of the present application, in step S3, the flexible substrate is selected from any one of PI, PET, and TPU.

[0010] As a further improvement of the present application, in step S4, the film thickness of the high-stress-resistant PMMA composite film is 100 nm to 1000 nm.

[0011] As a further improvement of the present application, in step S4, in the closed solvent vapor environment, the temperature is 20℃ to 40℃, the relative humidity is 30% to 60%, and the drying time is 6h to 24h.

[0012] As a further improvement of the present application, in step S4, the wavelength of the nano-wrinkled flow guide structure is 10nm to 150nm, and the amplitude is 10nm to 40nm.

[0013] As a further improvement of the present application, the preparation method further includes step S5 after step S4, which is a heat crosslinking treatment or ultraviolet crosslinking treatment on the high-stress-resistant PMMA composite film.

[0014] To achieve the above-mentioned purpose, the present application also provides a high-stress-resistant PMMA composite film prepared by the above-mentioned preparation method.

[0015] To achieve the above-mentioned purpose, the present application also provides a flexible OLED device, which includes a PI substrate, an ITO, an organic light-emitting layer, an Ag electrode, and the above-mentioned high-stress-resistant PMMA composite film arranged in layers.

[0016] The present application has the beneficial effect that the present application provides a preparation method of a high-stress-resistant PMMA composite film, which fully mixes polymethyl methacrylate, a solvent, and a functional nanofiller to form a film, and slowly dries the film in a closed solvent vapor environment, the vapor source being the above-mentioned solvent for dissolving polymethyl methacrylate, and a nano-wrinkled flow guide structure is induced on the surface of the film to obtain a high-stress-resistant PMMA composite film.

[0017] In the high stress-resistant PMMA composite film of the present application, the uniform dispersion of functional nanofillers in the PMMA matrix enables the optical film to have high optical transmittance, and the surface of the film induces the formation of a nano-corrugated flow guide structure to provide a directional release path for stress, solving the problem of uncontrollable stress concentration areas in non-textured designs. It is suitable for the use requirements of polarizing plates, encapsulation films, light control films and other devices in flexible OLEDs. DETAILED DESCRIPTION

[0018] As can be known from the background art, with the rapid development of flexible OLED technology towards foldable and rollable directions, the device thin film needs to withstand repeated bending (such as a folding angle of 0-180°) and rolling assembly (such as a rolling radius of several millimeters) for a long time, which puts forward more stringent requirements for the stress resistance, flexibility and optical stability of the thin film - not only needs to maintain the structural integrity after multiple deformations, but also needs to maintain stable high transmittance to ensure the display effect of the OLED device.

[0019] However, under the above dynamic scenarios, the existing PMMA thin film first causes stress to be unable to be dispersed directionally under external force due to its strong molecular chain rigidity and the absence of effective stress dissipation paths, which easily forms stress concentration in local areas (such as edges and small defects) of the thin film; stress concentration further causes the molecular chains in the local areas to be subjected to stress far exceeding their bearing limit, which causes the molecular chains to break and generates initial sites for micro-crack initiation; the presence of the initial sites further accelerates the stress aggregation at the crack tip, which causes the micro-crack to rapidly expand and penetrate the thin film, and finally causes the OLED device to have uneven display, packaging failure and other problems, which seriously affects the service life and use reliability of the device.

[0020] In the existing improved technical solutions, there are defects that it is difficult to balance the optical performance, flexibility and processing process compatibility: the cross-linking enhancement method improves the mechanical properties of the thin film by cross-linking the molecular chains, but the cross-linking process causes the cross-linking density of the PMMA molecular chains to be too high, which limits the movement ability of the molecular chain segments, and further causes the flexibility of the thin film to decrease significantly, the thin film to be easily brittle during bending due to the inability of the chain segments to adapt to the deformation, and the bending life to decrease substantially; the nano-filler enhancement method (such as the introduction of ZnO nanoparticles) can improve the mechanical properties by filler reinforcement, but the nano-filler is easy to agglomerate due to high surface energy, which causes the filler to be unevenly dispersed in the PMMA matrix, the light is scattered multiple times at the interface between the filler and the matrix, and finally causes the transparency of the thin film to decrease significantly, which cannot meet the requirement of high transmittance of the OLED device; the PMMA thin film without texture design has no specific stress flow guide structure on the surface, which cannot guide the stress to be released naturally along the preset path under the action of stress, which causes the stress concentration areas to be randomly distributed, the crack concentration areas to be uncontrollable, and it is difficult to improve the stress resistance of the key parts of the thin film.

[0021] Meanwhile, these prior art solutions generally lack precise regulation of the microstructure of the surface / interface of the PMMA film, fail to effectively link the physical regulation of the microstructure with the actual application requirements (such as high light transmittance, bending resistance, and adaptation to different component installations) of flexible electronic devices (such as OLEDs), and finally result in that the modified PMMA film is still difficult to meet the requirements of different devices such as polarizing sheets, packaging films, and light regulating films in flexible OLEDs in terms of comprehensive performance.

[0022] To solve the above problems, the application provides a high stress-resistant PMMA composite film, a preparation method, and a flexible OLED device. In the preparation method, a nano-corrugated flow guide structure is formed on the surface of the PMMA film, which can realize directional relief of stress, delay of crack initiation, and at the same time maintain high optical transmittance and flexibility, and adapt to the use requirements of devices such as polarizing sheets, packaging films, and light regulating films in flexible OLEDs.

[0023] To make the purposes, technical solutions, and advantages of the application clearer, the specific embodiments of the application are described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the application, rather than all the embodiments. Based on the embodiments in the application, all other embodiments obtained by those skilled in the art without creative labor fall within the protection scope of the application.

[0024] The application provides a preparation method of a high stress-resistant PMMA composite film, comprising the following steps: S1, fully dissolving polymethyl methacrylate in a solvent to obtain a first mixed solution, wherein the polymethyl methacrylate accounts for 5% to 12% in terms of mass percentage; preferably, the molecular weight of the polymethyl methacrylate is 80000 to 120000; S2, adding functional nano-filler to the first mixed solution, and mixing uniformly after magnetic stirring and ultrasonic dispersion in sequence to obtain a second mixed solution, wherein the functional nano-filler accounts for 0.01% to 10% in terms of mass percentage; preferably, the time for magnetic stirring is 1h to 3h, and the time for ultrasonic dispersion is 10min to 30min; S3, coating the second mixed solution in step S2 on a flexible substrate to form a film; S4, slowly drying the film formed in step S3 in a closed solvent vapor environment, and inducing the formation of a nano-corrugated flow guide structure on the surface of the film to obtain a high stress-resistant PMMA composite film, wherein the film thickness is 100nm to 1000nm, and the vapor source for forming the vapor environment includes the solvent in step S1.

[0025] Based on the above technical scheme, the polymethyl methacrylate (PMMA) is first fully mixed with a solvent, and then the functional nano filler is fully mixed by magnetic stirring and ultrasonic dispersion. The above mixing method can uniformly mix the functional nano filler and PMMA, can avoid the light scattering problem caused by uneven dispersion of nano filler, and can make the light uniformly transmit in the matrix. In addition, the second mixed solution after the above sufficient mixing is slowly dried after being placed in a closed solvent vapor environment formed by the same type of solvent in step S1. The problem of uneven solvent evaporation rate in the film can be avoided. The solvent vapor in step S1 can form a stable concentration gradient on the surface of the film, so that the solvent in the film evaporates at a slow and uniform rate, avoiding the solvent convection driving the filler migration and agglomeration, and ensuring that the functional nano filler always maintains a uniformly dispersed state during the film drying process. It will not cause new light scattering centers due to the decrease in dispersibility caused by the drying process.

[0026] The principle of the nano-wrinkled flow guiding structure formed in the above technical scheme is as follows: first, the vapor source of the closed solvent vapor environment is the same solvent as in step S1. This design allows the film to maintain a high concentration of target solvent vapor around it at all times. This atmosphere will form a solvent adsorption layer on the surface of the film. Compared with the inside of the film, the surface adsorption layer will significantly reduce the evaporation driving force of the solvent, thereby building a rate gradient in the thickness direction of the film, with slow evaporation of the surface solvent and fast evaporation of the internal solvent. As the drying process progresses, the solvent in the film continuously migrates to the surface due to its fast evaporation rate, while the surface solvent is inhibited by the high vapor concentration and cannot quickly escape, resulting in the PMMA molecular chains in the surface region of the film always being in a high swelling state (strong chain segment movement ability), while the internal region gradually shrinks (chain segment movement is limited) due to solvent loss. Thus, an interfacial stress difference between the surface swelling and the internal shrinking is generated between the surface and the inside of the film.

[0027] Secondly, this interfacial stress difference will continue to accumulate: when the tensile stress generated by the internal shrinkage exceeds the yield limit of the surface-swollen PMMA matrix, the surface chain segments will release stress through directional slip, but due to the rigidity of the PMMA molecular chain itself (especially after some solvent evaporation), the chain segment slip cannot completely eliminate the stress, but instead forms periodic stress concentration points in the surface region. At the same time, the solvent evaporation rate is stable and controllable in a closed environment, avoiding sudden stress increase or local rupture caused by too fast evaporation, allowing these stress concentration points to evolve slowly and orderly. The surface swelling region protrudes to both sides of the stress concentration point under the action of stress, and the internal shrinking region corresponds to a depression, gradually forming an initial micro-wrinkle structure.

[0028] Finally, as the drying process continues, the internal solvent of the film further volatilizes, the interfacial stress difference slowly increases, the amplitude of the initial micro-ridges gradually increases (the height difference between the protrusions and depressions expands), and the PMMA molecular chains slowly orient and arrange under the action of stress, so that the period of the ridges (the distance between adjacent protrusions) tends to be stable; and because the vapor environment concentration is uniform and the solvent volatilization rate is consistent, the stress evolution process of each region of the film surface is synchronized, and finally a nano-scale ridge flow structure with uniform distribution, controllable period and amplitude is formed, rather than disordered surface defects. Throughout the process, the solvent in step S1 is the key prerequisite for the vapor source - if the vapor source is another solvent, it may not form an effective surface adsorption layer due to poor compatibility with the PMMA matrix, or the solvent volatilization rate gradient may be disturbed, making it impossible to build a stable interfacial stress difference; a closed solvent vapor environment ensures the persistence and uniformity of the volatilization rate gradient, providing a stable stress evolution environment for the ordered formation of the ridge structure, and the two work together to ensure that the nano-ridge flow structure can be formed controllably and uniformly.

[0029] In summary, by designing a specific solution mixing step and slowly drying the film in a closed evaporation environment, on the one hand, the uniform dispersion of functional nanofillers in the PMMA matrix is ensured, the transparency of the film is ensured, and the high optical transmittance is maintained; on the other hand, by slowly drying the film in a closed evaporation environment, the solvent vapor forms a stable concentration gradient on the film surface, inducing the formation of a nano-ridge flow structure on the film surface. The structure provides a directional release path for stress, solving the problem of uncontrollable stress concentration areas in non-textured designs. When the film is bent or curled under stress, the stress is dispersed along the ridge flow structure, delaying the initiation of micro-cracks, and the resulting high-stress-resistant PMMA composite film also has good flexibility, meeting the use requirements of polarizing plates, encapsulation films, light control films and other devices in flexible OLEDs.

[0030] In an optional embodiment, in step S1, the solvent is selected from any one of trichloromethane, ethyl acetate, and an acetone / isopropyl alcohol mixture. Preferably, in the acetone / isopropyl alcohol mixture, the volume ratio of acetone to isopropyl alcohol is 1:1.

[0031] In an optional embodiment, in step S2, the functional nanofiller is selected from any one of the following: silica nanoparticles, graphene oxide, TEMPO-oxidized nanocellulose. Preferably, the silica nanoparticles have a particle size of 10-50 nm. Further, when silica nanoparticles are selected as the functional filler, the silica nanoparticles are 0.5-10% by mass percentage; when graphene oxide is selected as the functional filler, the graphene oxide is 0.01-5% by mass percentage; and when TEMPO-oxidized nanocellulose is selected as the functional filler, the TEMPO-oxidized nanocellulose is 0.5-3% by mass percentage.

[0032] Based on the above selection of the functional nanomaterials: the refractive index of the silica nanoparticles (about 1.46) is very small different from that of the PMMA matrix (about 1.49) (difference ≤0.03), and the light is almost not obviously refracted and reflected at the interface between the two, thereby reducing light scattering from the root; the graphene oxide is a single-atom layer two-dimensional sheet structure, and has a nanoscale thickness (about 0.34 nm) and a high light transmittance (the single-layer light transmittance can be above 97%), and when the sheet structure is uniformly dispersed in the PMMA matrix, the sheet structure is oriented and arranged along the film plane, and the light can smoothly penetrate along the plane direction and will not form a light scattering center due to particle agglomeration or excessively large size; the TEMPO-oxidized nanocellulose has a molecular structure containing a large number of polar groups such as hydroxyl and carboxyl groups, and can form a weak hydrogen bond interaction with the ester group of PMMA, and has a refractive index (about 1.50) highly close to that of PMMA, and the fiber diameter of the TEMPO-oxidized nanocellulose can be controlled to be 10-50 nm, which is much smaller than the wavelength of visible light (400-760 nm), and according to the Rayleigh scattering principle, the light scattering intensity caused by the small-size filler is extremely low, and the overall light transmittance of the film can be ensured.

[0033] Secondly, from the enhancement of the mechanical properties and stress resistance of the film, the three fillers can form synergistic reinforcement with the PMMA matrix through different structural advantages - the silica nanoparticles are rigid spherical fillers, and when uniformly dispersed in the PMMA matrix, can be used as mechanical support points to disperse local stress, and when the film is bent and curled, the particles can hinder the excessive slip of the PMMA molecular chain, reduce the microcrack initiation caused by stress concentration, and the spherical structure will not significantly damage the flexibility of the PMMA matrix, avoiding the embrittlement of the film; the two-dimensional sheet structure of the graphene oxide has a very high specific surface area (about 2630 m 2PMMA molecular chain, and can form a sheet-chain interwoven network structure through interface interaction, which can conduct stress along the sheet plane to avoid stress accumulation in a local area. Meanwhile, the sheet structure can form a macro-micro coordinated stress drainage system with the nano-ridged flow guiding structure of the film forming surface to further improve the stress resistance. TEMPO oxidized nanocellulose is a flexible fibrous filler, and its molecular chain can form a flexible combination with the PMMA molecular chain. When the film forming is stressed, the fibrous chain can absorb part of the stress through its own deformation to play a stress buffering role. Meanwhile, the fibrous structure can form an interwoven network in the PMMA matrix to enhance the tensile and bending resistance of the matrix and avoid film rupture after repeated deformation.

[0034] Finally, from the compatibility with the whole process chain, the three fillers can all adapt to the process requirement of solvent dissolution-vapor drying. The three fillers can all achieve good dispersion in the selected chloroform, ethyl acetate, and acetone / isopropyl alcohol mixture (1:1) of the application. Meanwhile, during the closed solvent vapor drying process, the size and density of the three fillers will not cause obvious sedimentation, and can maintain uniform distribution during the swelling-shrinking process of the PMMA matrix, without causing a decrease in dispersion due to the drying process, thereby ensuring that the fillers and the matrix can still cooperate when the nano-ridged flow guiding structure is formed, maintaining the integrity of the ridged structure and further improving the stress resistance of the film forming through the mechanical reinforcement of the fillers.

[0035] In summary, the selection of the three functional nanofillers is a multi-dimensional screening through optical compatibility, mechanical reinforcement, and process adaptability, which ensures that the fillers can not only cooperate with the PMMA matrix to achieve the core requirements of high light transmission and high stress resistance, but also adapt to the whole process, avoiding the introduction of new technical defects (such as light scattering, uneven dispersion, and process incompatibility), and finally ensuring the performance and preparation stability of the high stress resistant PMMA composite film.

[0036] In the optional embodiment, before the magnetic stirring and ultrasonic dispersion in step S2, a process of adding a non-ionic surfactant to the first mixed solution is further included. Preferably, the non-ionic surfactant is Tween-20. Further, the non-ionic surfactant is 0.05% to 0.5% by mass percentage. The non-ionic surfactant molecule contains a hydrophilic group and a lipophilic group, which can be adsorbed on the surface of the functional nanoparticles: the lipophilic group faces the particle surface, reduces the particle surface energy, and weakens the agglomeration force between particles; the hydrophilic group is compatible with the solvent (such as acetone / isopropyl alcohol mixture), and forms a solvation layer outside the particles to further block particle collision and agglomeration. At the same time, it can adjust the interface interaction between the particles and the PMMA matrix to avoid secondary agglomeration of the particles during mixing and drying, and provide support for the stability of the optical transmittance and mechanical properties of the film forming.

[0037] In an optional embodiment, in step S3, the flexible substrate is selected from any one of PI, PET, TPU; the film forming method is selected from any one of spin coating, slot die coating. Specifically, in the spin coating method: first, pre-laying is performed, the rotation speed of the flexible substrate in the pre-laying is 300 rpm-1000 rpm, and the time is 5 s-10 s; then, film forming is performed, the rotation speed of the flexible substrate in the film forming is 2000 rpm-4000 rpm, and the time is 30 s-90 s, and the prepared high stress-resistant PMMA composite film has a film thickness of 100 nm-1000 nm. In the slot die coating method: the liquid inlet speed is 0.1 ml / min-1.0 ml / min, and the coating speed is 0.5 mm / s-5 mm / s, and the prepared high stress-resistant PMMA composite film has a film thickness of 300 nm-1000 nm.

[0038] In an optional embodiment, in step S4, in the closed solvent vapor environment, the temperature is 20℃-40℃, the relative humidity is 30%-60%, and the drying time is 6h-24h.

[0039] In an optional embodiment, in step S4, the wavelength of the nano-wrinkled flow guide structure is 10 nm-150 nm, and the amplitude is 10 nm-40 nm.

[0040] In an optional embodiment, the preparation method further comprises step S5 after step S4, that is, the high stress-resistant PMMA composite film is subjected to thermal crosslinking treatment or ultraviolet crosslinking treatment. Preferably, in the thermal crosslinking treatment: the high stress-resistant PMMA composite film is placed in a vacuum or nitrogen atmosphere, the temperature is 60℃-90℃, and the time is 0.5h-2h; in the ultraviolet crosslinking treatment: the wavelength of the ultraviolet light is 254 nm, the light intensity is 10-20 mW / cm 2 , and the time is 10 min-30 min. The thermal crosslinking treatment and the ultraviolet crosslinking treatment can further improve the mechanical stability and the thermal stability of the composite film.

[0041] In order to verify that the technical scheme of the present application has excellent effects, the present application also provides the following examples.

[0042] Example 1 The present embodiment provides a preparation method of a high stress-resistant PMMA composite film, comprising the following steps: S1, 1 g of polymethyl methacrylate with a molecular weight of 120000 is fully dissolved in 10 ml of chloroform, and magnetic stirring is performed at room temperature for 2h until complete dissolution, to obtain a first mixed solution, and the polymethyl methacrylate accounts for 6.33% in terms of mass percentage; S2, 0.1 g of silica nanoparticles is added to the first mixed solution, and after magnetic stirring and ultrasonic dispersion, the second mixed solution is obtained, wherein the silica nanoparticles are 0.63% by mass fraction; S3, the second mixed solution in step S2 is coated on a flexible substrate to form a film, and a spin coater is used to spin coat the composite solution on a PI substrate, and the spin coating parameters are as follows: first step: 500 rpm, 5 s (uniform distribution); second step: 3000 rpm, 60 s (film formation); S4, the film in step S3 is placed in a closed solvent vapor environment for slow drying, and a nano-wrinkled flow guide structure is induced on the surface of the film to obtain a high-stress PMMA composite film with a thickness of 1000 nm, wherein the vapor source for forming the vapor environment is chloroform, the temperature in the closed solvent vapor environment is 25°C, the relative humidity is 30%, and the drying time is 8 h.

[0043] Example 2 The difference between this embodiment and example 1 is that the preparation method of the high-stress PMMA composite film further includes step S5, wherein the high-stress PMMA composite film is placed in a vacuum oven for heat crosslinking treatment, and the specific parameters are as follows: temperature 80°C, time 1 h.

[0044] Example 3 The embodiment provides a preparation method of a high-stress PMMA composite film, which comprises the following steps: S1, 1 g of polymethyl methacrylate with a molecular weight of 100000 is fully dissolved in 10 ml of ethyl acetate, and the first mixed solution is obtained by magnetic stirring at room temperature for 2 h until complete dissolution, wherein the polymethyl methacrylate is 10.00% by mass fraction; S2, graphene oxide aqueous dispersion and Tween-20 are sequentially added to the first mixed solution, and after magnetic stirring and ultrasonic dispersion, the second mixed solution is obtained by mixing uniformly, and then a high-speed emulsifier is used for treatment for 15 min, wherein the mass fraction of graphene oxide is 0.01%, and the mass fraction of Tween-20 is 0.1%; S3, the second mixed solution in step S2 is coated on a flexible substrate to form a film, and a slot-die is used to coat on PET: the coating rate is 1 mm / s; S4, the film in step S3 is placed in a closed solvent vapor environment for slow drying, and a nano-wrinkled flow guide structure is induced on the surface of the film to obtain a high-stress PMMA composite film with a thickness of 500 nm, wherein the vapor source for forming the vapor environment is ethyl acetate, the temperature in the closed solvent vapor environment is 40°C, the relative humidity is 50%, and the drying time is 12 h.

[0045] Example 4 The difference between this embodiment and Example 1 is that the preparation method of the high stress-resistant PMMA composite film further comprises step S5, that is, the high stress-resistant PMMA composite film is subjected to ultraviolet crosslinking treatment, and the specific parameters are as follows: the wavelength of the ultraviolet lamp is 254 nm, the light intensity is 15 mW / cm 2 , and the time is 15 min.

[0046] Example 5 The embodiment provides a preparation method of a high stress-resistant PMMA composite film, which comprises the following steps: S1, 0.8 g of polymethyl methacrylate with a molecular weight of 80000 is fully dissolved in 10 ml of an acetone / isopropyl alcohol mixed solvent (the volume ratio of acetone to isopropyl alcohol is 1:1), and magnetic stirring is performed at room temperature for 1 h until complete dissolution to obtain a first mixed solution, and the polymethyl methacrylate accounts for 9.22% in terms of mass percentage; S2, 0.1 g of TEMPO-oxidized nanocellulose is first dispersed in 2 ml of isopropyl alcohol, and then 0.1 g of the isopropyl alcohol mixture of TEMPO-oxidized nanocellulose is added to the first mixed solution, the TEMPO-oxidized nanocellulose has a diameter of 5 nm and a length of >1 μm, and after magnetic stirring and ultrasonic dispersion, the second mixed solution is uniformly mixed to obtain a second mixed solution, and the TEMPO-oxidized nanocellulose accounts for 0.97% in terms of mass percentage; S3, the second mixed solution in step S2 is coated on a flexible substrate to form a film, and spin coating is performed on a TPU flexible substrate, and the spin coating parameters are as follows: first step: 500 rpm, 5 s (uniform spreading); second step: 1000 rpm, 30 s (film forming); S4, the film formed in step S3 is placed in a closed solvent vapor environment for slow drying, and a nano-corrugated flow guide structure is induced on the surface of the film to obtain a high stress-resistant PMMA composite film, and the film thickness is 1000 nm, wherein the vapor source for forming the vapor environment is an acetone / isopropyl alcohol mixed solvent (the volume ratio of acetone to isopropyl alcohol is 1:1), the temperature in the closed solvent vapor environment is 20℃, the relative humidity is 40%, and the drying time is 24 h. Example 6 The difference between this embodiment and Example 1 is that the preparation method of the high stress-resistant PMMA composite film further comprises step S5, that is, the high stress-resistant PMMA composite film is subjected to heat crosslinking treatment in a nitrogen atmosphere, and the specific parameters are as follows: the temperature is 70℃, and the time is 2 h.

[0047] Comparative Example 1 A conventional PMMA film on the market is selected, and the surface of the PMMA film does not contain a nano-corrugated flow guide structure.

[0048] Comparative Example 2 The difference between this comparative example and Example 1 is that no silica nanoparticles were added, and the first mixed solution in step S1 was directly formed on a flexible substrate to obtain a high stress-resistant PMMA composite film.

[0049] Comparative Example 3 The difference between this comparative example and Example 1 is that the film formed in step S3 is directly and slowly dried without setting up a closed solvent vapor environment.

[0050] Comparative Example 4 The difference between this comparative example and Example 1 is that the film formed in step S3 is rapidly dried in a closed solvent vapor environment at a temperature of 100°C for 2 hours.

[0051] The ESC stress resistance time test and optical transmittance test were performed on Examples 1-6 and Comparative Examples 1-4 above. The specific test steps are as follows: ESC stress resistance test: The PMMA composite film of the above examples or comparative examples was cut into 150mm×25mm sizes and placed in a 23℃ / 50% RH environment for 24h to eliminate the initial effects; then the composite film was bent to a radius of 5mm using a fixture or testing machine, and then the sample was placed in an 85℃ / 85% RH environment for aging; finally, the presence of cracks was observed under a microscope, and the number of bends at which the first crack appeared was recorded.

[0052] Optical transmittance test: Preheat the spectrophotometer for 30 minutes, calibrate the instrument using air as a blank sample to ensure a stable baseline; cut a 10mm×10mm sample without scratches or bubbles from the PMMA composite film of the above examples or comparative examples, and place it in a 23℃ / 50% RH environment for 24 hours; then fix the sample flat on the sample holder to ensure complete coverage of the optical path and no wrinkles, and scan in the 400-700nm visible light band (or select a specific wavelength as needed), and record the transmittance data at different wavelengths; repeat the test 3 times and take the average value, while checking whether the sample is deformed due to the test, and finally sort the data to obtain the optical film transmittance result.

[0053] Haze test method: Haze reference standard GB / T 2410-2008 "Determination of light transmittance and haze of transparent plastics".

[0054] The parameters for ESC stress first crack time test and optical transmittance test of Examples 1-6 and Comparative Examples 1-4 are shown in Table 1.

[0055] Table 1

[0056] As shown in Table 1 above, the PMMA composite film prepared by the technical solution of this application has a bending life 3.3 times that of commercially available PMMA films without affecting optical transmittance and haze. Meanwhile, a comparison between Examples 1-6 and Comparative Examples 2-4 shows that silica nanoparticles, a sealed solvent vapor environment, and slow drying are all key factors affecting the technical effectiveness of this application.

[0057] Silica nanoparticles, as rigid spherical fillers, can act as mechanical support points when uniformly dispersed in the PMMA matrix, dispersing local bending stress, hindering excessive slippage of PMMA molecular chains, reducing the initiation of microcracks caused by stress concentration, and without compromising the flexibility of the matrix, thus avoiding embrittlement. The closed solvent vapor environment, using the solvent that dissolves PMMA as the vapor source, can form a stable concentration gradient and solvent adsorption layer on the film surface, creating an interfacial stress difference between surface swelling and internal contraction, orderly inducing the formation of nano-folded conductive structures, providing a directional release path for bending stress, and solving the problem of uncontrollable stress concentration areas. Slow drying (20℃~40℃, 6h~24h) can avoid filler migration and agglomeration caused by uneven solvent evaporation inside the film, ensuring uniform dispersion of nanoparticles and integrity of the nano-folded structure, while preventing stress surges or local cracking caused by excessively rapid evaporation. All three factors work together to improve the bending resistance of the PMMA composite film, and none can be omitted.

[0058] Flexible OLED devices were fabricated using the PMMA composite films prepared in Examples 1-6 and Comparative Examples 1-4. The device structure included a PI substrate, ITO, an organic light-emitting layer, an Ag electrode, and a PMMA composite film stacked together. The PMMA composite film was selected from any one of the PMMA composite films prepared in Examples 1-6 and Comparative Examples 1-4. The bending radius of the devices prepared in Examples 1-6 and Comparative Examples 1-4 was tested under the following conditions: a bending radius of 5 mm was set, and the device was cyclically bent 10,000 times. The brightness decay of the device was then observed. Additionally, the brightness retention rate of the device was tested after stable operation at 85℃ / 85%RH for 500 hours. The device test results are shown in Table 2.

[0059] Table 2

[0060] As shown in Table 2 above, the flexible OLED device prepared by the technical solution of this application exhibits a brightness decay rate of <5% after 10,000 cyclic bending cycles; simultaneously, after stable operation at 85℃ / 85%RH for 500 hours, the device brightness retention rate is >90%. It demonstrates excellent brightness retention.

[0061] In the high stress-resistant PMMA composite film of this application, functional nanofillers (such as silica nanoparticles) are uniformly dispersed to ensure high optical transmittance; its surface nano-folded flow-guiding structure can directionally release bending and environmental stress, reduce the initiation and propagation of microcracks in the film layer, and avoid uneven display and encapsulation failure due to film layer damage; some are also treated with thermal / ultraviolet crosslinking to improve mechanical and thermal stability, and can stably protect the internal structure of the device under cyclic bending and 85℃ / 85% RH environment, so the brightness decay is reduced and the retention rate is high.

[0062] In summary, the high-stress-resistant PMMA composite film prepared in this application has excellent high optical transmittance, bending stress, curling stress and flexibility, and is suitable for the use of devices such as polarizers, encapsulation films and light control films in flexible OLEDs.

[0063] The embodiments of the present invention have been described in detail above, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions, and variations can be made to these embodiments without departing from the principles and spirit of the present invention, and these variations still fall within the protection scope of the present invention.

Claims

1. A method for preparing a high-stress-resistant PMMA composite membrane, characterized in that, Includes the following steps: S1. Polymethyl methacrylate is fully dissolved in a solvent to obtain a first mixed solution, wherein the polymethyl methacrylate comprises 5% to 12% by mass. S2. Add functional nanofiller to the first mixed solution, and mix thoroughly by magnetic stirring and ultrasonic dispersion to obtain a second mixed solution. The functional nanofiller is 0.01% to 10% by mass percentage. S3. The second mixed solution from step S2 is coated onto a flexible substrate to form a film. S4. The film formed in step S3 is placed in a closed solvent vapor environment for slow drying, and a nano-wrinkled flow-guiding structure is induced on the surface of the film to obtain a high stress-resistant PMMA composite film. The vapor source for forming the vapor environment includes the solvent in step S1.

2. The preparation method according to claim 1, characterized in that, In step S1, the solvent is selected from any one of chloroform, ethyl acetate, and a mixture of acetone / isopropanol.

3. The preparation method according to claim 1, characterized in that, In step S2, the functional nanofiller is selected from any one of silica nanoparticles, graphene oxide, and TEMPO oxidized cellulose nanoparticles.

4. The preparation method according to claim 1, characterized in that, In step S2, before the sequential magnetic stirring and ultrasonic dispersion, a nonionic surfactant is added to the first mixed solution.

5. The preparation method according to claim 1, characterized in that, In step S3, the flexible substrate is selected from any one of PI, PET, and TPU.

6. The preparation method according to claim 1, characterized in that, In step S4, the thickness of the high stress-resistant PMMA composite film is 100nm to 1000nm.

7. The preparation method according to claim 1, characterized in that, In step S4, the temperature in the sealed solvent vapor environment is 20℃~40℃, the relative humidity is 30%~60%, and the drying time is 6h~24h.

8. The preparation method according to claim 1, characterized in that, In step S4, the wavelength of the nano-folded flow-guiding structure is 10nm to 150nm, and the amplitude is 10nm to 40nm.

9. The preparation method according to claim 1, characterized in that, The preparation method further includes step S5, which follows step S4, to perform thermal crosslinking or ultraviolet crosslinking treatment on the high stress-resistant PMMA composite film.

10. A high-stress-resistant PMMA composite membrane prepared by the preparation method according to any one of claims 1-9.

11. A flexible OLED device, characterized in that, It includes a PI substrate, ITO, an organic light-emitting layer, an Ag electrode, and the high stress-resistant PMMA composite film as described in claim 10, all stacked together.